14 The presence of diabetes as a comorbidity adversely affects the phenotypic expression of hypertrophic cardiomyopathy. (1st November 2021) - Jex, Nicholas; Chowdhary, Amrit; Thirunavukarasu, Sharmaine; Procter, Henry; Sengupta, Anshuman; Natarajan, Pavithra; Poenar, Ana-Maria; Swoboda, Peter; Xue, Hui; Cubbon, Richard M; Kellman, Peter; Greenwood, John P; et al.
Abstract : Background: Type 2 diabetes mellitus (DM) is associated with worsened clinical outcomes in hypertrophic cardiomyopathy (HCM) patients, although the mechanisms of this association are incompletely understood. Objectives: Utilizing 31 Phosphorus magnetic resonance spectroscopy ( 31 P-MRS) and cardiovascular magnetic resonance (CMR) in a prospective observational study of groups of patients with concomitant HCM and DM (HCM-DM), isolated HCM, isolated DM and healthy volunteers (HV), we tested the hypotheses that the collective impact of HCM and DM on the myocardium aggravates myocardial energetic impairment, contractile dysfunction, and fibrosis, and impairs coronary microvascular function. Methods: Seventy-five age- and sex-matched participants were recruited (20 HCM-DM, 20 HCM, 20 DM and 15 HV). HCM groups were matched for HCM phenotype. DM groups were matched for diabetes treatment, duration and HbA1c. Results: ESC sudden cardiac death risk scores were comparable between the HCM groups (HCM:2.2±1.5%, HCM-DM:1.9±1.2%; p=NS) and sarcomeric mutations were equally common. HCM-DM had the highest NT-proBNP levels (HV:42 ng/L[IQR:35–66 ng/L], DM:118 ng/L[IQR:53–187 ng/L], HCM:298 ng/L[IQR:157–837 ng/L], HCM-DM:726 ng/L[IQR:213–8695 ng/L]; p<0.0001). Left-ventricular ejection fraction, mass and wall thickness were similar between the HCM groups. HCM-DM displayed a greater degree of fibrosis burden with higher extracellular volume fraction and scar percentage, more significant reductions in global longitudinal strain and left atrial function compared to the isolated HCM. PCr/ATP was similarly decreased in the HCM-DM and DM (HV:2.17±0.49, DM:1.58±0.27, HCM:1.93±0.38, HCM-DM:1.54±0.27; p=0.0002). HCM-DM had the lowest stress myocardial blood flow (HV:2.06±0.42 ml/min/g, DM:1.95±0.41 ml/min/g, HCM:1.74±0.44 ml/min/g, HCM-DM:1.39±0.42 ml/min/g; p=0.0017). Conclusions: Comorbid diabetes adversely affects the HCM phenotype with greater reductions in myocardial energetics, perfusion, strain, increased scar burden and higher NT-proBNP levels compared to isolated HCM. Our findings suggest that specific, targeted therapeutic approaches may be useful in hypertrophic cardiomyopathy patients with diabetes comorbidity to improve clinical outcomes.